Genomics of New Ciliate Lineages Provides Insight into the Evolution of Obligate Anaerobiosis - Rotterová, Johana; Salomaki, Eric; Pánek, Tomáš; Bourland, William; Žihala, David; Táborský, Petr; Edgcomb, Virginia P; Beinart, Roxanne A; Kolísko, Martin; Čepička, Ivan (Current biology, 2020)
Oxygen plays a crucial role in energetic metabolism of most eukaryotes. Yet adaptations to low-oxygen concentrations leading to anaerobiosis have independently arisen in many eukaryotic lineages, resulting in a broad spectrum of reduced and modified mitochondrion-related organelles (MROs). In this study, we present the discovery of two new class-level lineages of free-living marine anaerobic ciliates, Muranotrichea, cl. nov. and Parablepharismea, cl. nov., that, together with the class Armophorea, form a major clade of obligate anaerobes (APM ciliates) within the Spirotrichea, Armophorea, and Litostomatea (SAL) group. To deepen our understanding of the evolution of anaerobiosis in ciliates, we predicted the mitochondrial metabolism of cultured representatives from all three classes in the APM clade by using transcriptomic and metagenomic data and performed phylogenomic analyses to assess their evolutionary relationships. The predicted mitochondrial metabolism of representatives from the APM ciliates reveals functional adaptations of metabolic pathways that were present in their last common ancestor and likely led to the successful colonization and diversification of the group in various anoxic environments. Furthermore, we discuss the possible relationship of Parablepharismea to the uncultured deep-sea class Cariacotrichea on the basis of single-gene analyses. Like most anaerobic ciliates, all studied species of the APM clade host symbionts, which we propose to be a significant accelerating factor in the transitions to an obligately anaerobic lifestyle. Our results provide an insight into the evolutionary mechanisms of early transitions to anaerobiosis and shed light on fine-scale adaptations in MROs over a relatively short evolutionary time frame.
Keywords: Anaerobiosis; phylogenomics; biologická evoluce; metagenome; genomika; anaerobiosis; Biological Evolution; anaerobióza; Genomics; mitochondrie; anoxia; mitochondria; Ciliophora; ciliates; symbiosis; transcriptome; protists; MROs; Mitochondria